Knowing - Black, Todd; Proyas, Alex; Summit Entertainment ([Santa Monica, California] : Summit Entertainment, 2009)
In 1959, as part of the dedication ceremony for a new elementary school, a group of students is asked to draw pictures to be stored in a time capsule. One mysterious girl fills her sheet of paper with rows of apparently random numbers instead. Fifty years later, a new generation of students examines the capsule's contents and the girl's cryptic message ends up in the hands of Caleb
screenplay by Ryne Douglas Pearson and Juliet Snowden & Stiles White
Cast: Nicolas Cage, Rose Byrne, Chandler Canterbury, Lara Robinson, Ben Mendelsohn
DVD format
With optional English, Chinese or Malay subtitles
Keywords: Time capsules -- United States -- Drama; Prophecies -- Drama; Disasters -- Drama; College teachers -- United States -- Drama; Fathers and sons -- United States -- Drama